Pengaruh Kualifikasi Pendidikan Terhadap Peningkatan Kinerja Pegawai Desa di Kecamatan Duhiadaa Kabupaten Pohuwato - Alpiana Hasan; Radia Hafid; Yulianti Tolarawe; Roy Hasiru; Abdulrahim Maruwae (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to identify the effect of educational qualifications on the improvement of performance of village apparatus in Duhiadaa Sub-district, Pohuwato Regency. This research employs a quantitative approach with descriptive research method. This research utilizes primary data collected through questionnaires distributed to village apparatus in Duhiadaa Sub-district, Pohuwato Regency. The sample consists of 50 respondents. The data analysis technique uses a simple linear regression analysis with the assistance of SPSS 21. The findings indicate a positive (8.755 > 2.010) and significant (0.000 < 0.05) effect between educational qualifications and the improvement of performance of village apparatus in Duhiadaa Sub-district, Pohuwato Regency. The coefficient of determination of the regression model is 0.615, which means that 61.5% of the variability in the improvement of the performance of village apparatus can be explained by educational qualifications. In other words, the better the educational qualifications of the village apparatus, the higher the performance they can achieve. This shows that education plays an important role in shaping the village apparatus's abilities, knowledge, and skills in effectively carrying out village government tasks. The remaining 38.5% is affected by other variables not examined in this research.